Matrix Metalloproteinase-9-Generated COOH-, but Not NH2-Terminal Fragments of Serum Amyloid A1 Retain Potentiating Activity in Neutrophil Migration to CXCL8, With Loss of Direct Chemotactic and Cytokine-Inducing Capacity - Gouwy, Mieke; De Buck, Mieke; Abouelasrar Salama, Sara; Vandooren, Jennifer; Knoops, Sofie; Pörtner, Noëmie; Vanbrabant, Lotte; Berghmans, Nele; Opdenakker, Ghislain; Proost, Paul; Van Damme, Jo; Struyf, Sofie (Frontiers in Immunology, 2018)
Serum amyloid A1 (SAA1) is a prototypic acute phase protein, induced to extremely high levels by physical insults, including inflammation and infection. Human SAA and its NH2-terminal part have been studied extensively in the context of amyloidosis. In contrast, little is known about COOH-terminal fragments of SAA. Intact SAA1 chemoattracts leukocytes via the G protein-coupled receptor formyl peptide receptor like 1/formyl peptide receptor 2 (FPRL1/FPR2). In addition to direct leukocyte activation, SAA1 induces chemokine production by signaling through toll-like receptor 2 (TLR2). We recently discovered that these induced chemokines synergize with intact SAA1 to chemoattract leukocytes in vitro and in vivo. Gelatinase B or matrix metalloproteinase-9 (MMP-9) is also induced by SAA1 during infection and inflammation and processes many substrates in the immune system. We demonstrate here that MMP-9 rapidly cleaves SAA1 at a known consensus sequence that is also present in gelatins. Processing of SAA1 by MMP-9 at an accessible loop between two alpha-helices yielded predominantly three COOH-terminal fragments: SAA1(52-104), SAA1(57-104) and SAA1(58-104), with a relative molecular mass of 5884.4, 5327.3 and 5256.3, respectively. To investigate the effect of proteolytic processing on the biological activity of SAA1, we chemically synthesized the COOH-terminal SAA fragments SAA1(52-104) and SAA1(58-104) and the complementary NH2-terminal peptide SAA1(1-51). In contrast to intact SAA1, the synthesized SAA1 peptides did not induce interleukin-8 (IL-8)/CXCL8 in monocytes or fibroblasts. Moreover, these fragments possessed no direct chemotactic activity for neutrophils, as observed for intact SAA1. However, comparable to intact SAA1, SAA1(58-104) cooperated with CXCL8 in neutrophil activation and migration, whereas SAA1(1-51) lacked this potentiating activity. This cooperative interaction between the COOH-terminal SAA1 fragment and CXCL8 in neutrophil chemotaxis was mediated by FPR2. Hence, proteolytic cleavage of SAA1 by MMP-9 fine-tunes the inflammatory capacity of this acute phase protein in that only the synergistic interactions with chemokines remain to prolong the duration of inflammation.